Bulbophyllum sect. Racemosae (Orchidaceae) in Vietnam with the description of the new species, B. minhquanii and the new national record, B. albidostylidium - Huynh, Huu Duc; Averyanov, Leonid V.; Maisak, Tatiana V.; Nguyen, Quoc Bao; Nguyen, van Canh; Dang, van Son; Nguyen, Truong Giang; Truong, Quang Tam; Truong, Ba Vuong (Phytotaxa, 2025)
The paper provides a taxonomic assessment of Bulbophyllum section Racemosae in Vietnam, accompanied by an identification key for all species currently recognized in the country. Information on type specimens, distribution, habitat and phenology (when available), as well as relevant taxonomic notes are presented for each accepted species, accompanied by plates with analytical photos. Bulbophyllum minhquanii is described as new to science, and B. albidostylidium (identified earlier as B. putii) is reported as a new national record. In total, 14 species of B. sect. Racemosae, of which five are endemic, are documented for Vietnam based on previous and current studies. The occurrences of B. macrocoleum and B. morphologorum in Vietnam remain uncertain and require verification by additional collections.